Author Correction: Subpixel three-dimensional laser imaging with a downscaled avalanche photodiode array using code division multiple access - Fan Xu (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s42005-021-00520-8.